Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s13014-015-0358-z
|View full text |Cite
|
Sign up to set email alerts
|

Salvage radiotherapy in patients with local recurrent esophageal cancer after radical radiochemotherapy

Abstract: PurposeThe aim of this study was to evaluate the salvage radiotherapy outcome in patients with local recurrent esophageal cancer after radical radiochemotherapy (RCT).MethodsA total of 114 patients with local recurrent esophageal squamous cell carcinoma after initial radical RCT were retrospectively analyzed. Fifty-five (55) patients belonged to the salvage radiotherapy group (SR group) and 59 patients to the non-salvage radiotherapy group (NSR group).ResultsThe median survival time after-recurrence was 4 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
46
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 24 publications
(36 reference statements)
12
46
4
Order By: Relevance
“…This study is believed to be the rst to compare the effects of 50 Gy and 60 Gy re-irradiation dose on the survival of patients with LRESCC with radiation history. Our results showed that most patients (68/125, 54.4%) had recurrence within 2 years after initial (chemo)radiotherapy, which was consistent with previous reports [4,8,13,16]. Jingu et al reported that the 3-year survival rate and median survival time of 33 patients with LRESCC receiving 60 Gy (range, 18-70 Gy) re-radiotherapy were 17.8% and 16 months, respectively [15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study is believed to be the rst to compare the effects of 50 Gy and 60 Gy re-irradiation dose on the survival of patients with LRESCC with radiation history. Our results showed that most patients (68/125, 54.4%) had recurrence within 2 years after initial (chemo)radiotherapy, which was consistent with previous reports [4,8,13,16]. Jingu et al reported that the 3-year survival rate and median survival time of 33 patients with LRESCC receiving 60 Gy (range, 18-70 Gy) re-radiotherapy were 17.8% and 16 months, respectively [15].…”
Section: Discussionsupporting
confidence: 91%
“…Increasing the dose of radiation showed an encouraging outcome. Our results are also better compared with those of other studies [4,13,15]. The reason may be that higher doses of radiation were more bene cial for tumor control.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Esophageal cancer is the seventh most common cause of cancer-related mortality in Japan, with an estimated 11,746 deaths in 2008 (12). Re-irradiation salvage therapy, with or without chemotherapy, for recurrent esophageal carcinoma after definitive chemoradiotherapy yielded reasonable results in this small group of patients, extending MST from the expected 9.9 months (2) to 13.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Re-RT was a strong risk factor for EF (P=0.003, OR=3.926 ,95%CI: 1.615-9.548). Zhou et al [29] reported 55 patients with recurrent EC happened EF after re-RT. The study found that re-RT could improve survival rate of patients, but the incidence of EF was as high as 20% (11/55).…”
Section: Discussionmentioning
confidence: 99%